The girl who played with fire - Larsson, Stieg, 1954-2004.; Keeland, Reg, 1943- (New York : Alfred A. Knopf, 2009)
Two reporters responsible for a sex-trafficking expos ǎre murdered, and the fingerprints on the murder weapon belong to Lisbeth Salander, prompting the magazine's publisher, Mikael Blomkvist, to launch his own investigation to vindicate Salander.
Originally published: Stockholm : Norstedts, 2006.